Mortality from liver cancer and liver disease in haemophilic men and boys in UK given blood products contaminated with hepatitis C. UK Haemophilia Centre Directors' Organisation. - Darby, S; Ewart, D; Giangrande, P; Spooner, R; Rizza, C; Dusheiko, G; Lee, C; Ludlam, C; Preston, F (1997)
BACKGROUND: Most people with haemophilia who were treated with blood products before the introduction of virus-inactivation procedures were infected with the hepatitis-C virus (HCV). However, there is little quantitative information about the long-term effects on mortality of such infection. METHODS: We carried out a cohort study of mortality from liver cancer and liver disease in 4865 haemophilic men and boys in the UK. They were treated between 1969 and 1985 with blood products carrying a high risk of HCV infection, and were followed up from first recorded exposure to Jan 1, 1993. FINDINGS: Based on death-certificate information, mortality was 16.7 times higher than in the general population for liver disease (95% CI 12.5-22.0; 51 deaths), and 5.6 times higher (1.8-13.0; five deaths) for liver cancer. For men and boys with severe haemophilia who were not infected with HIV-1, the cumulative risks of death from chronic or unspecified liver disease or from liver cancer in the 25 years since first recorded exposure to high HCV-risk products were 1.4% (0.7-3.0) at all ages, and 0.10% (0.01-0.7), 2.2% (0.8-6.1), and 14.3% (4.5-40.9) for those with first recorded exposure at ages under 25, 25-44, and 45 or older. For those with haemophilia and HIV-1 infection, the corresponding risks were 6.5% (4.5-9.5) at all ages, and 3.8% (2.1-6.8), 17.1% (10.0-28.5), and 18.7% (6.4-47.6) in the three age-groups. In those with severe haemophilia, age-standardised all-cause mortality was stable during 1969-84 but increased during 1985-92 in both HIV-1-infected and HIV-1-uninfected groups. Among those not infected with HIV-1, the increase in all-cause mortality resulted largely from deaths attributed to chronic or unspecified liver disease or liver cancer in men aged over 45. INTERPRETATION: There is an emerging risk of mortality from liver disease and liver cancer in the UK haemophilia population in individuals both infected and uninfected with HIV-1, which probably results from infection with hepatitis C.